The Influence of Free Time and Job Satisfaction on Casual Employees' Performance in Serving Customers at the JW Marriott Hotel Medan - Muhammad Risqi Ananda; Muhammad Lathief Ilhamy Nasution; Khairina Tambunan (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
The purpose of this study was to determine the contribution of leisure time and job satisfaction to the performance of casual workers. The analysis technique used was multiple linear regression. Data were obtained from several casual employees at JW Marriott Hotel Medan using a questionnaire. The analysis in this study showed conflicting findings. Individual analyses yielded conflicting results: leisure time was found to have a significant positive impact on performance, while job satisfaction had no statistically significant effect. Consequently, when tested together (F-test), the combined effect of both variables was insignificant. This is consistent with the relatively low coefficient of determination (R²) of 18.7%, indicating that the contribution of both variables in explaining employee performance is quite limited, with the remaining 81.3% of the variance explained by factors outside the research model. This study focused on casual employees in the hospitality sector, specifically at JW Marriott Hotel Medan, who enjoy high flexibility but face uncertainty regarding hours and workload. This study found that good work, leisure, and management policies can reduce stress and fatigue levels and increase motivation. This impacts customer satisfaction, strengthens the hotel's reputation, and encourages economic growth by increasing revenue and tourist attraction.